Redefinisi Peran Guru Menuju Pendidikan Islam Bermutu - Muhammad Saleh; Ahmad Edwar; Maratusyolihat Maratusyolihat (Alim | Journal of Islamic Education, 2021)
The dichotomy of secular science and religious science changes the mindset of the Muslim community in religion. From the classical period, which saw Islam as a comprehensive teaching, it has turned into an understanding that views Islam as a religion that is only ritual oriented. It is understood that education is a process that has continuity and is consciously carried out to prepare a generation that has balanced knowledge and values. On the other hand, the negative impact of modern life cannot be avoided by modern humans, especially from the aspect of education. For this reason, various elements in education must continue to maintain existing linkages to achieve predetermined goals. Low participation and public concern for the advancement of the world of education must end, along with the realization of the concept of school based management or SBM. Another aspect that must be prepared is the quality of teachers. Conceptually, teachers have three functions, namely cognitive, moral and innovative. In order to become an ideal figure in Indonesia, teachers must meet eight indicators, namely theological principles, formal principles, functional principles, cultural principles, comprehensiveness principles, substantial principles, social principles and identity principles.